Monensin intoxication due to intraruminal boluses in beef cattle: retrospective analysis of 7 outbreaks - Tettamanti, Agustina (2025)
Monensin is an ionophore antibiotic well known for its multiple benefits in cattle diets. Toxic monensin Lethal Dose 50 (LD50) concentrations in cattle are reported from 26 mg/kg BW. Intraruminal monensin boluses consist of controlled-released capsules, often administered to beef or dairy cattle. Seven outbreaks were analyzed, all occurring in Buenos Aires province between 1997 and 2024 affecting steers in extensive or semi-extensive grazing systems. Clinical signs appeared one to five months after boluses application and included loss of appetite, decay, recumbency, reluctance to move, tachypnea, isolation, muscle tremors, ear drooping and sudden death. Twelve necropsies were performed, and gross findings included pale multifocal streaks myocardium of both ventricles, edema in cavities and mesenteries, hepatomegaly, and diffusely non collapsed or inflated lung with interlobular edema. Microscopically, the most characteristic lesion present in all 12 necropsies was necrotizing cardiomyopathy in different stages of regeneration, some of them being polyphasic. Masson trichrome stain revealed fibrous connective tissue in extensive multiple areas replacing cardiac muscle cells. Mean serum CPK was considered moderately to highly elevated. Herein in all 7 outbreaks, boluses apparently failed to release pills correctly. In conclusion, though toxicosis after failure of intraruminal boluses in grazing cattle are rare, it is important to describe the occurrence of cases when release bolus mechanism fails, causing intoxication that evolves from subacute to chronic, with characteristic pathological findings of polyphasic muscle lesions.